An approach to ethic dilemmas of geriatric medicine. - Alain Francisco Morejón Giraldoni; Jirlén Moreno Torres; Esteban Hernández Barrio; Yoel Padrón Vega; Carlos Daniel Mayor Igarza; Aimee Seife Echevarria (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
The bioethical formulation is based on three (or four) principles: beneficence (and no maleficence, after some authors), justice and autonomy. In spite of multiple received criticisms this proposal have been enriched and strengthened. From this point, sanitary activity and the medical practice as well, can be considered as activities with a clear social insertion, thus susceptible of an ethical analysis which goes beyond of the narrow margins of the professional ethics. Population aging as a worldwide phenomenon will bring about a major demand of the assistance and social services. New ethic dilemmas could emerge from the demographic changes, related to the intergenerational, family and health services relationship overall. General practitioners and particularly gerontologist should be prepared to face this medical an ethical challenges.